HUBUNGAN POLA ASUH ORANGTUA DENGAN STATUS IDENTITAS DIRI REMAJA - Yanti, Afril '; ', Herlina '; Rahmalia HD, Siti ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Pattern of guidance parents is the way parents providing guidance or instruction to adolescent in accordance with the norms and values in society. Pattern of guidance parents is one of the determining factors of identity in adolescent. The aim of this research was identify the correlation between pattern of guidance parents with adolescent identity in SMAN 6 Pekanbaru. The design research was correlation descriptive with cross sectional approach. The total sample in the research was 87 adolescences using stratified random sampling technique. The instrument used was a questionnaire pattern of guidance parents 18 statements and adolescent identity questionnaire 20 statements which has been tested for validity and reliability. The data was analized by univariat with frequency distribute and bivariat analysis with Chi Square. The result showed there were 28,7% adolescences with democratic parenting and 74.7% adolescences were in active identity status. This research found an correlation between pattern of guidance parents with adolescent (p value 0,000 < 0,05). The result of this research recommend to the school and parents can collaborateto monitor the growth and development in adolescent in achieving a active identity. Keywords: Adolescent, Identity, Pattern of guidance parents